Pengaruh Kepemimpinan dan Standar Operasional Prosedur Terhadap Kinerja Karyawan Studi Kasus Pada Departemen Housekeeping Hotel Crowne Plaza Semarang - Inggar Rizal Megantar; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2016)
Leadership and standard operating procedures are important factors for the achievement of employee performance. Hotel Crowne Plaza Semarang is a company engaged in the field of hospitality and strives to provide the best service, and therefore requires human resources with good performance.This type of research is explanatory research, with a population of 34 permanent employees in the department Housekeeping Hotel Crowne Plaza Semarang and everything sampled by census. Data were collected through questionnaires with Likert scale measurement. Data analysis method used is correlation, simple and multiple linear regression using SPSS 20.0.This study concluded SOP leadership and influence on employee performance partially or simultaneously. Variable leadership has a greater influence than the SOP.Suggestions can be submitted is the Hotel Crowne Plaza Semarang especially the Housekeeping department needs to update our SOP and leadership are implemented.